Analisis Kualitas Laba dan Resiliensi Finansial PT Bumi Serpong Damai Tbk: Pendekatan Akuntansi Forensik Periode 2020–2024 - Iwan Gunawan; Rei Adrianto; Sri Retnaning Sampurnaningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The national property industry underwent significant structural adjustments during the transition from the pandemic crisis to economic normalization. This study aims to evaluate the earnings quality of PT Bumi Serpong Damai Tbk (BSDE) throughout the 2020-2024 fiscal period. Employing a quantitative descriptive approach, this research deconstructs financial statements using vertical and horizontal analyses, coupled with adjustments for non-recurring items. The findings reveal a surge in Net Profit of 124.06% in 2024, reaching IDR 4.36 trillion. However, an in-depth forensic analysis discloses that approximately 35% of this profit (IDR 1.55 trillion) stems from a one-off gain on bargain purchase (keuntungan pembelian diskon) related to subsidiary acquisitions. Fundamentally, the core business performance remains robust, evidenced by a 19.56% growth in Operating Revenue and cost structure optimization. This study concludes that while the headline profit figures are impressive, investors must distinguish between sustainable operational recovery and incidental strategic gains to assess long-term value accurately.